2009
DOI: 10.3904/kjim.2009.24.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of On-Treatment Triglyceride Level in Patients Treated by Percutaneous Coronary Intervention for Non-ST-Segment Elevation Acute Coronary Syndrome

Abstract: Background/AimsThe use of statins in patients with acute coronary syndrome (ACS) has increased, and reduced levels of low-density lipoprotein cholesterol (LDL-C) lead to lower coronary event rates. We studied the effect of lipid levels during statin treatment on prognosis in patients with ACS and percutaneous coronary intervention (PCI).MethodsBetween January 2005 and May 2007, 325 ACS patients who underwent PCI and received statins were evaluated. We measured serum lipid levels at baseline and 4 weeks. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The data on subjects with established CHD are limited only to many small studies with relatively short follow-up periods, which have shown inconclusive results. [22][23][24] For example, in a study by Cheng et al 22 on 247 patients with ST-segment-elevation MI who were treated with primary PCI and followed up for a period of 1.23 to 1.4 years, higher levels of triglycerides (>150 versus <150 mg/dL) were paradoxically associated with a lower rate of overall major adverse cardiac events. This discrepancy could be explained by different study populations (acute versus stable CHD patients), different outcome measures, and chance, reflecting a post hoc finding.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The data on subjects with established CHD are limited only to many small studies with relatively short follow-up periods, which have shown inconclusive results. [22][23][24] For example, in a study by Cheng et al 22 on 247 patients with ST-segment-elevation MI who were treated with primary PCI and followed up for a period of 1.23 to 1.4 years, higher levels of triglycerides (>150 versus <150 mg/dL) were paradoxically associated with a lower rate of overall major adverse cardiac events. This discrepancy could be explained by different study populations (acute versus stable CHD patients), different outcome measures, and chance, reflecting a post hoc finding.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…This discrepancy could be explained by different study populations (acute versus stable CHD patients), different outcome measures, and chance, reflecting a post hoc finding. Yun et al 24 showed in 325 patients who underwent PCI and received statins, that high triglycerides levels (>150 mg/ dL), 4 weeks after PCI, are an independent predictor of major adverse cardiac events (HR, 4.01; CI, 1.85-9.06). Similar to our results, results by Sprecher et al 23 showed that after coronary artery bypass grafting, triglycerides levels are predictive of long-term all-cause mortality risk (mostly 5-year mortality), yet the results were not fully adjusted for HDL-C.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%